Haribhaktivilāsa of Sanātana Gosvāmin, Volume Two : Morning to Afternoon Duties (Chapters 6-10). Critical Edition and Annotated Translation - Broo, Måns (Asian Studies E-Books Online, Collection 2026., 2026)
Sanātana Gosvāmin's Haribhaktivilāsa (ca. 1540) describes the normative ritual life of a Vaiṣṇava devotee. As it is one of the first Sanskrit texts of Gauḍīya Vaiṣṇava tradition begun by Śrī Kṛṣṇa Caitanya (1486-1533) it presents a fascinating meeting between this ecstatic new religious movement and older, Brahminical tradition. On the basis of eleven manuscripts, this important text has now been for the first time been critically edited. This volume is centred on the main worship in the morning, which is described in great detail -- including a whole chapter on flowers.